The role of marketing and advertising in the integration and development of creative industries in the international classification (Journal of Economic Research & Business Administration, 2024)
This article highlights the impact of creative industries on economic development, with a particular focus on marketing and advertising. The creative industries have been the subject of much recent discussion due to their potential to stimulate innovation and draw in talented individuals. The creative economy of Kazakhstan is expanding, but it has not yet established advertising and marketing as core economic activities. They also explore the potential for an international classification system that recognizes advertising as a separate sector of the creative economy. The research contributes to the understanding of how marketing and advertising influence creative industries, highlighting the importance of marketing tactics to both attract and retain creative professionals, as well as promote economic growth and innovation.Through a systematic approach, comparative analysis, and logical reasoning, the study examines existing literature on creative industries. The presented model integrates the marketing and advertising components into the value chain of production and distribution of creative products/services. And the results highlight new challenges faced by and solutions to principal stakeholders of a creative economy. Although marketing and advertising are not extensively discussed in Kazakhstan, they are instrumental in the development and distribution of innovative products and services.It includes international examples and discusses current trends in Kazakhstan's creative economy, demonstrating the practical value of this work for regional strategy formulation. The implementation of these measures could lead to better marketing and advertising practices in Kazakhstan's creative industries, which could boost their economic growth and global competitiveness.Key words: creative industries, creative economy, international classification, advertising, marketing strategies, place branding.